E-gov.ph examining e-governance in the Philippines through the websites and social media sites of selected national government agencies - Olaño, Karmela Mica N. 1993- (2014)
"e-Governance has been said to be one of the tools to achieve good governance. With the recent public clamor for greater transparency, accountability and participation, this study examines how e-Governance is manifested on the websites and social media sites of selected Philippine national government agencies. It seeks to determine whether these selected websites and social media sites have the potential for achieving good governance through e-Governance. The Systems theory, Backus' e-Governance model and Sandoval-Almazan and Gil-Garcia's Evolutionary Approach to e-Governance served as the theoretical foundations of this research. A survey was conducted with 150 respondents from three randomly selected cities in Metro Maila and the websites and social media sites of the DFA, NSO and BIR were content analyzed. Results of both survey and content analysis showed that the current website and social media site features of the selected national government agencies do not promote public participation. Although e-Governance has not yet been well-actualized in the government websites and social media sites, it was found to have a potential for steering the country towards good governance."